2010
DOI: 10.1891/1933-3196.4.3.e31
|View full text |Cite
|
Sign up to set email alerts
|

L’EMDR dans le traitement de la douleur chronique

Abstract: La douleur chronique peut réduire considérablement la qualité de vie, engendrant dépression, anxiété et troubles du sommeil ; elle peut déclencher des processus neuroplastiques qui influencent la régulation de la douleur. La présente étude examine le traitement EMDR (Eye Movement Desensitization and Reprocessing) de 38 patients souffrant de douleur chronique, en 12 séances hebdomadaires de 90 minutes. Une batterie de questionnaires auto-administrés, portant sur la qualité de vie, l’intensité de la douleur et l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(Arias Suarez et al, 2020 ; Brennstuhl et al, 2016 ; 2017a ; Gerhardt et al, 2016 ; Grant, 2000 ; Grant & Threlfo, 2002 ; Mazzola et al, 2010 ) (Arias Suarez et al, 2020 ; Mazzola et al, 2010 ) (Gerhardt et al, 2016 ) (Gerhardt et al, 2016 ) (Grant & Threlfo, 2002 ) (Arias Suarez et al, 2020 ; Mazzola et al, 2010 ) (Arias Suarez et al, 2020 ; Mazzola et al, 2010 ) (Brennstuhl et al, 2016 ; 2017a ) (Supplementary Table 4A). (Arias Suarez et al, 2020 ; Gerhardt et al, 2016 ) (Brennstuhl et al, 2016 )…”
Section: Resultsmentioning
confidence: 99%
“…(Arias Suarez et al, 2020 ; Brennstuhl et al, 2016 ; 2017a ; Gerhardt et al, 2016 ; Grant, 2000 ; Grant & Threlfo, 2002 ; Mazzola et al, 2010 ) (Arias Suarez et al, 2020 ; Mazzola et al, 2010 ) (Gerhardt et al, 2016 ) (Gerhardt et al, 2016 ) (Grant & Threlfo, 2002 ) (Arias Suarez et al, 2020 ; Mazzola et al, 2010 ) (Arias Suarez et al, 2020 ; Mazzola et al, 2010 ) (Brennstuhl et al, 2016 ; 2017a ) (Supplementary Table 4A). (Arias Suarez et al, 2020 ; Gerhardt et al, 2016 ) (Brennstuhl et al, 2016 )…”
Section: Resultsmentioning
confidence: 99%
“…Bilateral alternative stimulation (BAS) is a visual technique mainly applied during a psychotherapeutic approach called eye movement desensitization and reprocessing (EMDR) for post-traumatic stress disorder (PTSD) treatment ( 139 , 147 ), although growing evidence tends to highlight possible applications of EMDR to relieve pain in patients living with acute or chronic painful conditions ( 44 , 80 , 130 , 131 , 42 , 114 ).…”
Section: Sensory Stimulimentioning
confidence: 99%
“…In addition, nine weekly sessions of 1 h of EMDR can effectively decrease pain levels and their affect, as well as increase pain control in patients suffering from chronic pain for at least 6 months ( 44 ). In 38 patients living with chronic pain, it has been shown that 12 weekly EMDR sessions of 90 min were able to significantly decrease the amount of medication needed and to improve the quality of life (e.g., pain, physical activity, vitality, social interaction, emotional management) ( 80 ).…”
Section: Sensory Stimulimentioning
confidence: 99%